Research, innovation and technological performance in Germany - EFI Report 2008 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2008)
Research and innovation are extremely important for Germany. New insights are generated by research, and new ways of creating value are opened up by technical, organisational, and other innovations. Production, value-creation and employment tend to increase much more in companies which are highly innovative. The public sector can become more efficient and customer-oriented through the implementation of innovations, which also have a positive influence on people's welfare and their quality of life. Against this background, Germany's politicians have increasingly been considering how best to promote research and innovation, and where the country ranks in the international innovation contest. The Federal Government of Germany therefore decided in 2006 to establish an independent Commission of Experts on Research and Innovation (EFI), with the remit to analyse the structures, trends, performance, and prospects of the German research and innovation system, and to formulate policy recommendations for its further development. This report is the result of our work to achieve this goal. – – Forschung und Innovation (F&I) sind für Deutschland von herausragender Bedeutung. Durch Forschung werden neue Erkenntnisse geschaffen, durch Innovationen – technische, organisatorische oder andere Neuerungen – werden neue Formen der Wertschöpfung erschlossen. In innovationsstarken Unternehmen wachsen Produktion, Wertschöpfung und Beschäftigung in weitaus stärkerem Maß als in innovationsschwachen. Der öffentliche Sektor kann durch Innovationen an Effizienz und Kundenorientierung gewinnen. Wohlstand und Lebensqualität der Menschen werden durch Innovationen positiv beeinflusst. Vor diesem Hintergrund stellt sich für die Politik zunehmend die Frage, wie sie Forschung und Innovation fördern kann und welche Position Deutschland im internationalen Innovationswettbewerb einnimmt. Die Bundesregierung hat deshalb im Jahr 2006 die Einrichtung einer unabhängigen Expertenkommission Forschung und Innovation (EFI) beschlossen. Sie hat die Aufgabe, Strukturen, Trends, Leistungsfähigkeit und Perspektiven des deutschen Forschungs- und Innovationssystems zu analysieren sowie Handlungsempfehlungen für dessen Weiterentwicklung zu erarbeiten. Das hiermit vorgelegte Gutachten ist das zentrale Instrument zur Erfüllung dieser Aufgabe.
Keywords: 330; Innovation; Forschung; Technischer Fortschritt; Deutschland